Stability Analysis of Predator-prey Model with Stage- structured and the Effect of Harvesting - Noorehan Yaacob; Faridah Mustapha (Annals of Mathematical Modeling, 2022)
Predator-prey model is the study to show the interaction between prey and preda- tor. A stage-structured model is introduced where the mature and immature of the species is considered. Also, the effect of harvesting is taken into account for sustainable development. The model in this paper is explained by using the ordinary differential equations to show the dynamic behavior of the predator and prey. Hence, the predator-prey model with stage- structured in prey with the effect of harvesting in predator is considered in this paper. In analyzing the model, the stability of the equilibrium point is obtained and described by using the properties of eigenvalues and Routh-Hurwitz criteria. Finally, numerical simulations are given to verify the analytical results with the help of graphical illustrations.